A pilot study to identify links between genetic variation and shoulder pain and dysfunction after breast cancer radiotherapy - McLarty, Callum (Department of Human Biology, 2021)
Introduction – Treatment for breast cancer is associated with a risk of chronic shoulder and upper limb morbidity in up to 30% of patients. There is currently no consensus for the possible reason for this often repeated finding in the literature. Previous research has suggested that development of fibrotic tissue in response to cancer treatments such as surgery and radiotherapy could be an underlying cause of musculoskeletal dysfunction and pain. This study investigated if any genetic variants in several key fibrosis-modulating genes could be shown to be associated with risk of upper limb musculoskeletal dysfunction and pain in breast cancer survivors. Participants and Methods – A cross sectional study design was employed, using a candidate gene approach. A total of 326 South African breast cancer survivors were recruited from a tertiary hospital in the Western Cape (343 total, minus 17 samples with insufficient data collected). Each participant was scored for symptom severity using the shoulder pain and disability index (SPADI) questionnaire. Participants were then grouped for symptom severity using low, med or high SPADI scores. The low SPADI group served as controls (controls n=273, cases n=70). Participants were invited to donate a blood sample from which DNA was extracted. Each DNA sample was genotyped at seven polymorphic sites; three in TGF-ß, two in ATM, one in SOD2 and one in XRCC1, using PCR technologies and TaqMan allelic-discrimination probes. The resultant genotypes were analysed using multivariate analysis, including inferred haplotype analysis to search for association to shoulder pain and morbidity after treatment. A logistic regression analysis was also performed to investigate the association between SPADI score and age of participant. Results – When participant age was compared with symptom severity, it was found that younger participants were more likely to have moderate-to-severe symptoms than older participants. There was a significant difference in the minor allele frequencies between case and control groups for the rs4880 (C>T, SOD2) polymorphism. The T allele was present more in the case group than in controls, with minor allele frequencies of 0.67 vs 0.55 respectively. No other independent associations were noted for any of the remainder variants tested. When haplotypes were inferred for genes SOD2 and ATM, combinations between the rare alleles at rs4880 and rs1800058 (C>T, ATM) were associated (F=4.35, pT and ATM rs1800058 is recommended for further study, in addition to the rs4880 polymorphism in SOD2. These novel results are suggesting that there may be an association between fibrotic genes and the development of upper limb sequelae after treatment for breast cancer. A larger case-control study would be required to validate and explore these findings.